Distribusi Sistem Kelistrikan pada PT Waagner Biro Indonesia (WBI) - Siti Annisa Nindia Larasati; Mohammad Fatkhurrokhman; Siswo Wardoyo (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Distribution of electricity is very important, because there’s a need for electrical energy to consumers over time. The purpose of this study is to find out how the distribution of electricity from the center to PT. Waagner Biro Indonesia and know the specifications of the distribution support panels contained in the panel room. The research methods used are observation methods, interview methods, and literature study. It can be concluded that The voltage source comes from PLN with a voltage of 20kV which is classified as medium voltage and 1,110,000 VA or 1.11 mVA which is distributed to Cubicle WBI. The distribution of electrical energy sources from PLN to the panel room will be through the PLN cubicle in the concrete substation. Incoming PLN is obtained from the MV Cubicle PLN in the concrete substation to the incoming MVMDB (Medium Voltage Main Distribution Board) via the N2XSEBY 20 kV cable with a distance of 242.5 m from the concrete substation to the incoming PLN. At Outgoing PLN connected to a step-down transformer from a voltage of 20kV lowered to 380V/220V. And the source of electrical energy received from the WBI Cubicle is 20 kV, then the source of electrical energy is stepped down from 20 kV to 380 V, then it is distributed to LVMDP.